Improvement in soil physical environment enhances crop productivity - Tyagi, S. K.; Singh, Ravender (Indian Farming, 2015)
Soil health has recently captured the attention of farmers/researchers as soil degradation from intensive cultivation, mechanization, limited crop rotations, and lack of organic matter additions have reduced yield potential. One of the reasons for such phenomenon is the deterioration of soil physical environment. Hence, attention towards the improvement of soil physical health is essential for continuously increasing and sustaining high crop productivity levels. The adoption of the above discussed agricultural practices extends the promise to safe guard the soil physical environment for sustainable agricultural production in the country.